Steel, products made from said steel and method of making the same
By adjusting the chemical composition and thermal mechanical treatment of martensite aging steel, combined with surface treatment, the problems of high material costs and insufficient mechanical properties in the prior art are solved, and the effect of providing excellent mechanical properties and good surface properties at low cost is achieved.
Patent Information
- Application Number
- CN202310042396.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2015-10-15
- Filing Date
- 2016-10-17
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2036-10-17
AI Technical Summary
Existing martensite aging steels have difficulty achieving the optimal tradeoff between high mechanical properties and low material costs, especially in terms of fatigue strength and surface treatment capabilities.
By adjusting the chemical composition of the steel, ensure that the content of Ni, Mo and Co is within a specific range, and combined with thermomechanical treatment and surface treatment, a new type of martensite aging steel with excellent mechanical properties and good surface properties is formed.
Achieving extremely high tensile strength, fatigue strength and improved surface properties at low material costs, particularly in the nitriding behavior, delaying the occurrence of cracking under circulating loads.
Smart Images

Figure CN116024505B_ABST
Abstract
Description
[0001] This application is a divisional application of application number 201680060149.6 filed on October 17, 2016, and the invention name is “Steel, products made of said steel and manufacturing method thereof”. Technical Field
[0002] The present invention relates to the field known as "maraging steels", to steels used in particular in applications requiring one or more of the following properties: excellent mechanical properties (very high fatigue strength, high yield strength and high fracture strength), simplicity of heat treatment and dimensional stability after these treatments, ease of welding and good formability. Background Art
[0003] These maraging steels are characterized by a martensitic structure which is able to be hardened after aging by precipitation of intermetallic phases suitable for obtaining high mechanical properties during aging.
[0004] Generally, the known maraging steels of the M 250 type include those having the following typical composition (as all compositions indicated in the present text are expressed in percentage by weight): Ni=18%, Co=9%, Ti=0.45% (known as X2NiCoMo18-9-5 steel), the remainder being generally iron and impurities arising from the manufacture, with Ti being included as a hardening element. They are particularly used to form parts having excellent properties both as solid parts (engine shafts, centrifugal blades, etc.) and as high-performance precision parts: watch springs, fencing blades, parts of automatic transmission belts, especially of the CVT (Continuous Transmission) type for cars or vehicles in general, or machine tools and other rotating machines. For applications where the parts are subjected to fatigue, it is common practice to subject the parts to nitriding, carbonitriding, shot peening, carburizing to harden the surface in addition to aging.
[0005] From document EP-B1-1 339 880, it is known that a Ti-free maraging steel has the following composition: Ni=12% to 24.5%; Mo=2.5%; Co=4.17%; Al≤0.15%; Ti≤0.1%; N≤30 ppm; Si≤0.1%; Mn≤0.1%; C≤50 ppm; S≤10 ppm; P≤50 ppm; H≤3 ppm; O≤10 ppm; the remainder is Fe and impurities resulting from the production, of which Ni+Mo is 20% to 27%; Co%×Mo% is 50 to 200; Ti%×N%≤2.10 -4, which is produced by a process comprising treatments of the VIM type (vacuum induction melting) and / or VAR type (vacuum arc remelting), optionally these processes being combinable with ESR slag remelting (electroslag remelting). These steels are subsequently transformed by hot working and cold working to obtain very thin strips (e.g. 1 mm or less). After the component has undergone shaping, precipitation hardening is carried out to impart critical mechanical properties to the component; subsequent surface treatment can impart enhanced surface properties in terms of fatigue stress, static friction, dynamic wear, etc.
[0006] Compared with the previously known maraging steels containing approximately 18% Ni, 9% Co, 5% Mo, 0.5% Ti and some Al, these steels in document EP - B1 - 1 339 880 are distinguished from the previous ones by a higher fatigue strength (in the aged, nitrided state) related to a controlled inclusion population and fatigue durability. More specifically, the target mechanical properties of the cold - rolled product are Ar > 2.5%, Rp 0.2 < 1140 MPa, Rm < 1480 MPa; in the aged state, Rp 0.2 > 1770 MPa, Rm > 1800 MPa; finally, in the nitrided state, the target properties are Ar > 1%; Rm > 1930 MPa.
[0007] It is known from document EP - B1 - 2 180 073 that maraging steels for CVT belts having high fatigue strength and tensile strength have the following composition: C ≤ 100 ppm; Si ≤ 0.1%; Mn ≤ 0.1%; P ≤ 0.01%; S ≤ 50 ppm; Ni = 17 - 22%; Cr = 0.1% - 4.0%; Mo = 3.0% - 7.0%; Co = 10.0% - 20.0%; Ti ≤ 0.1%; Al ≤ 0.05%; N ≤ 300 ppm; O ≤ 50 ppm; 0 < B ≤ 0.01%; optionally up to 0.01% of Ca, up to 0.005% of Mg, up to 0.01% of Zr, the balance being Fe and impurities, wherein Co / 3 + Mo + 4Al is 8.0% - 15.0%. Preferably, the heat treatments and thermomechanical treatments applied impart to them a very fine grain ASTM 10 or finer.
[0008] Likewise, it is known from the applicant's patent application PCT / IB2015 / 052975 that maraging steels with a low carbon content and a controlled inclusion population, in combination with a Co content of 1% - 25% and a Mo content of 1% - 12%. The sum of the hardening elements Mo + Co that can be added is 20% - 29%, and Ni + Co + Mo is at least 29%. However, in the best recommendations of this application, the content of high - cost elements is still high. Summary of the Invention
[0009] The object of the present invention is to provide a new type of maraging steel, the material costs associated with high mechanical properties being as low as possible. In other words, the steel should present an optimal compromise between relatively low material costs and very good inherent mechanical properties (related to excellent surface properties, for example in terms of nitriding behavior) for applications in which the final product is particularly subject to fatigue, compared to the steels just described. For the above-mentioned applications, sufficient tensile strength and / or fatigue strength is required in combination with improved surface properties, especially the ability to be treated on the surface to form a nitriding, carbonitriding, carburizing, shot peening or other layer. This layer must be able to provide residual stresses on the surface, thereby being able to delay cracking under cyclic loads through compression of the surface layer. For example, the effect of the surface treatment can be evaluated via the hardness imparted to the surface of the product, the relative level of residual stresses and the type of phases formed.
[0010] For this purpose, the subject of the invention is a steel, characterized in that it has the following composition in weight percent:
[0011] 10.0%≤Ni≤24.5%, preferably 12.0%≤Ni≤24.5%;
[0012] 1.0%≤Mo≤12.0%, preferably 2.5%≤Mo≤7.0%;
[0013] 1.0%≤Co≤18.0%, preferably 4.0%≤Co≤18.0%, more preferably 7.0%≤Co≤16.0%, further preferably 8.0%≤Co≤15.0%;
[0014] 14.0%≤Mo+Co+Si+Mn+Cu+W+V+Nb+Zr+Y+Ta+Cr+C+Al+B+Ti+N≤29.0%, preferably 15.0%≤Mo+Co+Si+Mn+Cu+W+V+Nb+ Zr+Y+Ta+Cr+C+Al+B+Ti+N≤27.0%, better 17.0%≤Mo+Co+Si+Mn+Cu+W+V+Nb+Zr+Y+Ta+Cr+C+Al+B+Ti+N≤26.0%;
[0015] 21.5%≤Ni+Co+Mo≤47.5%, preferably 25.0%≤Ni+Co+Mo≤40.0%;
[0016] Trace amount ≤Al≤4.0%, preferably trace amount ≤Al≤2.0%;
[0017] Trace amount ≤Ti≤0.1%;
[0018] Trace amount ≤N≤0.010%;
[0019] Trace amount ≤ Si ≤ 4.0%, preferably ≤ 2.0%;
[0020] Trace amount ≤ Mn ≤ 13.0%, preferably trace amount ≤ Mn ≤ 4.0%; more preferably 0.14% ≤ Mn ≤ 4.0%;
[0021] Preferably Si+Mn≥0.13%;
[0022] Trace ≤C≤0.03%;
[0023] Trace amount ≤ S ≤ 0.0020%, preferably trace amount ≤ S ≤ 0.0010%;
[0024] Trace ≤P≤0.005%;
[0025] Trace amount ≤ B ≤ 0.01%;
[0026] Trace ≤H≤0.0005%;
[0027] Trace ≤O≤0.03%;
[0028] Trace amount ≤Cr≤5.0%, preferably 0.01%≤Cr≤5.0%; more preferably 0.1%≤Cr≤5.0%;
[0029] Trace ≤Cu≤4.0%;
[0030] Trace amount ≤ W ≤ 6.0%;
[0031] Trace amount ≤ Zr ≤ 4.0%;
[0032] Trace amount ≤Ca≤0.1%;
[0033] Trace ≤Mg≤0.8%;
[0034] Trace amount ≤ Nb ≤ 4.0%; preferably Nb ≤ 2.0%;
[0035] Trace ≤V≤4.0%;
[0036] Trace ≤Ta≤4.0%;
[0037] Trace ≤ Y ≤ 4.0%;
[0038] Preferably, the trace amount is ≤Al+Si+Cu+Nb+Mn+V+Ta+Cr+W+C+B+Y+Zr+Ti+N≤14.0%, and more preferably, the trace amount is ≤Al+Si+Cu+Nb+Mn+V+Ta+Cr+W+C+B+Y+Zr+Ti+N≤8.0%; further preferably, 0.14%≤Al+Si+Cu+Nb+Mn+V+Ta+Cr+W+C+B+Y+Zr+Ti+N≤8.0%;
[0039] Preferably Al+Cr≥0.1%, more preferably ≥0.17%;
[0040] The rest is iron and impurities brought about by its manufacture;
[0041] And characterized in that when the steel is in the form of a hot-worked component or a hot-rolled plate, the 650mm 2 Polished surface and in the form of cold rolled steel plate of 800mm 2 The inclusion group observed by image analysis of the polished surface does not contain non-metallic inclusions with an equivalent diameter greater than 10 μm, and preferably does not contain non-metallic inclusions with an equivalent diameter greater than 8 μm.
[0042] Another subject of the invention is a method for producing a steel product, characterized in that:
[0043] Prepare a remelting electrode using steel having a composition corresponding to the above composition;
[0044] remelting the electrode using a single or multiple remelting process to obtain a remelted electrode;
[0045] Subjecting the remelted electrode to at least one hot working at 1050° C. to 1300° C. to obtain a hot-worked plate or a hot-worked strip;
[0046] And optionally, the hot-processed plate or the hot-processed strip is heat-treated.
[0047] The hot-worked plate or strip, which may be optionally heat treated, has a Vickers hardness of 285 Hv10 or more, evaluated along a cross section of the component or hot-rolled plate.
[0048] Subsequently, the hot processed sheet or the hot processed strip may be subjected to one or more cold rolling passes to obtain a sheet or strip having a thickness of 2 mm or less, preferably 1 mm or less.
[0049] The sheet or strip may be subjected to at least one heat treatment between two cold rolling passes or after the last cold rolling pass.
[0050] The cumulative cold reduction rate of each pass is at least 30%, preferably at least 40%.
[0051] The hot rolled or cold rolled sheet or strip, which may be optionally heat treated, may have a martensitic structure of at least 70%, a tensile strength of 2030 MPa or more, a compensated yield strength of 2000 MPa or more, and a uniform elongation of 1% or more.
[0052] The hot-rolled or cold-rolled sheet or strip, which may have been heat treated, is cut and optionally formed.
[0053] The optionally heat treated, cut and optionally formed hot-rolled or cold-rolled sheet or strip may be subjected to a hardening treatment at 400° C. to 600° C. for 30 minutes to 5 hours, preferably at 420° C. to 550° C. for 30 minutes to 2 hours.
[0054] After hardening, the cut and optionally shaped, optionally heat-treated sheets or strips are subjected to a surface treatment to improve the dynamic yield strength.
[0055] The surface treatment may be carburizing, or gas nitriding, or ion nitriding, or carbonitriding, or shot peening.
[0056] The grain size of the optionally heat treated hot rolled sheet or strip, or the optionally heat treated cold rolled sheet or strip may be 5 ASTM or finer, preferably 10 ASTM or finer.
[0057] Another subject matter of the invention is a hot-rolled and optionally heat-treated steel product, characterized in that it has the following composition in weight percent:
[0058] 10.0%≤Ni≤24.5%, preferably 12.0%≤Ni≤24.5%;
[0059] 1.0%≤Mo≤12.0%, preferably 2.5%≤Mo≤7.0%;
[0060] 1.0%≤Co≤18.0%, preferably 4.0%≤Co≤18.0%, more preferably 7.0%≤Co≤16.0%, further preferably 8.0%≤Co≤15.0%;
[0061] 14.0%≤Mo+Co+Si+Mn+Cu+W+V+Nb+Zr+Y+Ta+Cr+C+Al+B+Ti+N≤29.0%, preferably 15.0%≤Mo+Co+Si+Mn+Cu+W+V+Nb+ Zr+Y+Ta+Cr+C+Al+B+Ti+N≤27.0%, better 17.0%≤Mo+Co+Si+Mn+Cu+W+V+Nb+Zr+Y+Ta+Cr+C+Al+B+Ti+N≤26.0%;
[0062] 21.5%≤Ni+Co+Mo≤47.5%, preferably 25.0%≤Ni+Co+Mo≤40.0%;
[0063] Trace amount ≤Al≤4.0%, preferably Al≤2.0%;
[0064] Trace amount ≤Ti≤0.1%;
[0065] Trace amount ≤N≤0.010%;
[0066] Trace amount ≤ Si ≤ 4.0%, preferably ≤ 2.0%;
[0067] Trace amount ≤Mn≤13.0%, preferably trace amount ≤Mn≤4.0%;
[0068] Trace ≤C≤0.03%;
[0069] Trace amount ≤ S ≤ 0.0020%, preferably trace amount ≤ S ≤ 0.0010%;
[0070] Trace ≤P≤0.005%;
[0071] Trace amount ≤ B ≤ 0.01%;
[0072] Trace ≤H≤0.0005%;
[0073] Trace ≤O≤0.03%;
[0074] Trace amount ≤Cr≤5.0%, preferably 0.01%≤Cr≤5.0%; more preferably 0.1%≤Cr≤5.0%;
[0075] Trace ≤Cu≤4.0%;
[0076] Trace amount ≤ W ≤ 6.0%;
[0077] Trace amount ≤ Zr ≤ 4.0%;
[0078] Trace ≤ Y ≤ 4%;
[0079] Trace amount ≤Ca≤0.1%;
[0080] Trace ≤Mg≤0.8%;
[0081] Trace amount ≤ Nb ≤ 4.0%; preferably Nb ≤ 2.0%;
[0082] Trace ≤V≤4.0%;
[0083] Trace ≤Ta≤4.0%;
[0084] Trace ≤ Y ≤ 4.0%;
[0085] Preferably, the trace amount is ≤Al+Si+Cu+Nb+Mn+V+Ta+Cr+W+C+B+Y+Zr+Y+Ti+N≤14.0%, more preferably, the trace amount is ≤Al+Si+Cu+Nb+Mn+V+Ta+Cr+W+C+B+Y+Zr+Y+Ti+N≤8.0%; further preferably, 0.14%≤Al+Si+Cu+Nb+Mn+V+Ta+Cr+W+C+B+Y+Zr+Ti+N≤8.0%;
[0086] Preferably Al+Cr≥0.1%, more preferably ≥0.17%;
[0087] The rest is iron and impurities brought about by its manufacture;
[0088] And characterized in that, for hot-worked parts or hot-rolled plates, the 650mm 2 The inclusion population observed when the polished surface is subjected to image analysis preferably does not contain non-metallic inclusions having an equivalent diameter greater than 8 μm.
[0089] Another subject of the invention is a hot-rolled and optionally heat-treated steel product, characterised in that it has a martensitic structure of at least 70%, a tensile strength of 2030 MPa or more, a compensated yield strength of 2000 MPa or more, a uniform elongation of 1% or more and a Vickers hardness of 285 Hv10 or more, the hardness being assessed along a cross section of the component or hot-rolled sheet.
[0090] Another subject of the present invention is a cold-rolled steel sheet or strip, characterized in that it has the following composition in weight percentage:
[0091] 10.0%≤Ni≤24.5%, preferably 12.0%≤Ni≤24.5%;
[0092] 1.0%≤Mo≤12.0%, preferably 2.5%≤Mo≤7.0%;
[0093] 1.0%≤Co≤18.0%, preferably 4.0%≤Co≤18.0%, more preferably 7.0%≤Co≤16.0%, further preferably 8.0%≤Co≤15.0%;
[0094] -14.0%≤Mo+Co+Si+Mn+Cu+W+V+Nb+Zr+Y+Ta+Cr+C+Al+B+Ti+N≤29.0%, preferably 15.0%≤Mo+Co+Si+Mn+Cu+W+V+Nb+ Zr+Y+Ta+Cr+C+Al+B+Ti+N≤27.0%, better 17.0%≤Mo+Co+Si+Mn+Cu+W+V+Nb+Zr+Y+Ta+Cr+C+Al+B+Ti+N≤26.0%;
[0095] 21.5%≤Ni+Co+Mo≤47.5%, preferably 25.0%≤Ni+Co+Mo≤40.0%;
[0096] Trace amount ≤Al≤4.0%, preferably Al≤2.0%;
[0097] Trace amount ≤Ti≤0.1%;
[0098] Trace amount ≤N≤0.010%;
[0099] Trace amount ≤ Si ≤ 4.0%, preferably ≤ 2.0%;
[0100] Trace amount ≤Mn≤13.0%, preferably trace amount ≤Mn≤4.0%;
[0101] Trace ≤C≤0.03%;
[0102] Trace amount ≤ S ≤ 0.0020%, preferably trace amount ≤ S ≤ 0.0010%;
[0103] Trace ≤P≤0.005%;
[0104] Trace amount ≤ B ≤ 0.01%;
[0105] Trace ≤H≤0.0005%;
[0106] Trace ≤O≤0.03%;
[0107] Trace amount ≤Cr≤5.0%, preferably 0.01%≤Cr≤5.0%; more preferably 0.1%≤Cr≤5.0%;
[0108] Trace ≤Cu≤4%;
[0109] Trace amount ≤ W ≤ 6.0%;
[0110] Trace amount ≤ Zr ≤ 4.0%;
[0111] Trace amount ≤Ca≤0.1%;
[0112] Trace ≤Mg≤0.8%;
[0113] Trace amount ≤ Nb ≤ 4.0%; better Nb ≤ 2.0%;
[0114] Trace ≤V≤4.0%;
[0115] Trace ≤Ta≤4.0%;
[0116] Trace ≤ Y ≤ 4.0%;
[0117] Preferably, the trace amount is ≤Al+Si+Cu+Nb+Mn+V+Ta+Cr+W+C+B+Y+Zr+Ti+N≤14.0%, and more preferably, the trace amount is ≤Al+Si+Cu+Nb+Mn+V+Ta+Cr+W+C+B+Y+Zr+Ti+N≤8.0%; further preferably, 0.14%≤Al+Si+Cu+Nb+Mn+V+Ta+Cr+W+C+B+Y+Zr+Ti+N≤8.0%;
[0118] Preferably Al+Cr≥0.1%, more preferably ≥0.17%;
[0119] The rest is iron and impurities brought about by its manufacture;
[0120] And the characteristic is that, for 800mm 2 The inclusion group observed by image analysis of the polished surface does not contain non-metallic inclusions with an equivalent diameter greater than 10 μm, and preferably does not contain non-metallic inclusions with an equivalent diameter greater than 8 μm.
[0121] It may have been subjected to at least one heat treatment after cold rolling.
[0122] The hot or cold rolled and optionally heat treated plate or strip may have a tensile strength of 2030 MPa or more, a compensated yield strength of 2000 MPa or more, and a uniform elongation of 1% or more. On the other hand, two-phase steel grades may require conditioning heat treatment and may exhibit lower mechanical properties after a certain degree of thermal cycling; however, these steel grades maintain improved performance under dynamic stress in service (through strain hardening and phase transformation) in combination with enhanced nitriding.
[0123] A further subject of the invention is a steel product, characterised in that it comes from an optionally shaped hot-rolled or cold-rolled sheet or strip of the type described above and in that it has been subjected to a surface treatment for improving the resistance to dynamic stresses which can cause surface cracking.
[0124] The surface treatment may be selected from carburizing, gas nitriding, ion nitriding, carbonitriding, and shot peening.
[0125] A further subject of the invention is a turbine shaft or a hot-worked transmission component, characterised in that said shaft or said component comprises at least one element made of a hot-worked product of the type described above.
[0126] Another subject of the invention is a drive belt, characterized in that it comprises at least one element made of a cold-rolled sheet or strip of the type described above, or at least one element made of a product of said sheet or strip.
[0127] It may be a drive belt of the CVT type for motor vehicles.
[0128] Another subject of the invention is a steel product subjected to hot working and optional heat treatment of the aforementioned type, or a cold rolled sheet or strip optionally subjected to heat treatment of the aforementioned type, characterized in that the grain size of the product or the grain size of the sheet or strip is 5 ASTM or finer, preferably ASTM 10 or finer.
[0129] As will be understood, in order to obtain targeted savings compared to the known prior art, the present invention reduces the mandatory or preferred maximum content of some elements, such as Co, and even Mo, compared to previous recommendations, and complements this reduction by the mandatory presence of hardening elements of the Cu, Nb, Mn, Si, Al, Ta, V, W type within defined contents and other elements not usually used systematically. These steel grades are able to obtain mainly a martensitic structure, which is typical of maraging steels, or a mixed austenitic-ferritic structure. The present invention is a compromise between material costs and mechanical properties, and such effects are obtained thanks to the composition of the steel, the thermomechanical treatment applied or the mechanical properties of the heat treatment, and the controlled population of non-metallic inclusions (mainly oxides, sulfides, nitrides) which meet specific criteria of quantity, distribution, size distribution and composition.
[0130] Said population is obtained after careful preparation of the liquid metal by combining different production processes and operator control conditions. In particular, it is recommended to use new or substantially undegraded refractory linings for vessels such as furnaces and ladles for liquid metal treatment, and to avoid contact between the liquid metal and the atmosphere by using vacuum treatment and protective neutral gas (argon) when the metal is exposed to air or will be exposed to air for the purpose of preventing reoxidation and renitridation. The agitation of the liquid metal in the production vessel must be controlled (by electromagnetic means or especially by injection of neutral gas) so as to accelerate the precipitation of inclusions, but not to capture oxidized impurities or other impurities, especially due to corrosion of the refractory lining, or to capture impurities falling from the slag above the liquid metal. These precautions are known per se to those skilled in the art, but it is important that the best of the known prior art should be applied in the present invention to avoid oxide, nitride or sulfide inclusions exceeding acceptable thresholds such as those determined in the present invention in the final product.
[0131] The steels of the invention, especially when they have a high Cr or Mn content, or more particularly when they have a high Cr and Mn content, prove particularly suitable for subsequently obtaining a nitrided layer with mechanical properties (low plastic deformation capacity), thus conferring important advantages, especially when these steels are preferably used to produce components of CVT drive belts. From this point of view, Cu and Nb are also advantageous. BRIEF DESCRIPTION OF THE DRAWINGS
[0132] The present invention will be better understood by reading the following description with reference to the accompanying drawings:
[0133] Figure 1 Shown is the hardening precipitate obtained from sample Inv 15 after gas nitriding as depicted by thin section transmission electron microscopy;.
[0134] Figure 2The characterization of the nitrided layer by measuring the surface microhardness level on a reference sample and a steel sample of the invention is shown;
[0135] Figure 3 The characterization of the nitrided layer by measuring the residual surface stress on a reference sample and a steel sample according to the invention is shown;
[0136] Figure 4 The elastic behavior of the nitrided layer expressed as the indentation depth and the residual depth is shown in the scratch test performed on two samples of the invention in the nitrided state.
[0137] Figure 5 Shown in Figure 4 Changes in acoustic emission when scratch testing is performed on the same sample with increasing loads.
[0138] Figure 6 The elastic behavior of four samples of the invention and one reference sample, all in the nitrided state, during a scratch test is shown. DETAILED DESCRIPTION
[0139] The composition of the steel (expressed in weight percent) was determined based on the following considerations.
[0140] The Ni content is 10.0% to 24.5%, preferably 12.0% to 24.5%. In this case:
[0141] Firstly, by conventional heat treatment, a highly martensitic structure is obtained, i.e., meaning that at least 30%, and more preferably at least 50%, of the martensitic structure can be seen on the micrograph on the surface of the structure; a Ni content exceeding 24.5% in combination with the desired contents of the other elements will not result in such a structure, regardless of the heat treatment applied;
[0142] Secondly, after precipitation hardening, advantageous properties, in particular ductility, expansion, yield strength, K1C toughness, are obtained for the envisaged application; a minimum Ni content of 10.0%, with the associated defined proportions of Co, Mo and other metal elements being suitable for obtaining such properties; a minimum Ni content of 12.0% is further preferred to obtain this effect satisfactorily.
[0143] The Mo content is 1.0% to 12.0%. This element can achieve structural hardening by forming Fe2Mo, MoNi3 and fine and dispersed intermetallic compounds during aging. Optimally, the Mo content is 2.5% to 7.0% in order to obtain both a highly significant Mo effect and an intermetallic compound of the best size to ensure uniformity of mechanical properties. The upper limit of Mo depends on the need to retain a large part of the martensitic structure that can be hardened by aging.
[0144] Since this element is expensive and since its effect on structural stiffening can be partially ensured by other, more economical elements, it is advantageous not to add any excess amounts.
[0145] Mo also plays a role in the formation and properties of the nitriding layer, wherein the nitriding layer contains fine and dispersed particles depending on the nitriding process conditions (such as Mo2N, Fe x Mo y N z Different types of sediments (such as types of sediments).
[0146] The Co content is 1.0% to 18.0%. This element stabilizes the martensitic structure, increases the solidus temperature, and indirectly participates in hardening by promoting the precipitation of intermetallic compounds. If the proportion of Co used is higher than 18.0%, the addition will result in high costs (expensive price of Co) and if the content of other elements is within the scope of the present invention at the same time, the properties of the steel will be significantly improved. Preferably, the Co content is 4.0% to 18.0%, more preferably 7.0% to 16.0%, and further preferably 8.0% to 15.0%.
[0147] If Co and Mo have controlled contents which are modest compared to the usual amounts, their effect must be completed by adding one or more hardening elements Si, Mn, Cu, W, V, Nb, Zr, C, Al, B, Y, Ta, Cr, Ti, N within the ranges defined in the rest of the invention. This is one of the ways according to the invention to keep the properties at a high level due to structural hardening while the cost of the steel is reduced, in particular if these alternative hardening elements are selected from those of the lowest cost. The same applies here as mentioned above with respect to Mo.
[0148] As a result of the need for sufficient amounts of Co, the total amount of hardening elements Mo+Co+Si+Mn+Cu+W+V+Nb+Zr+Ta+Cr+C+Al+B+Y+Ti+N is 14.0% to 29.0%, preferably 15.0% to 27.0%, more preferably 17.0% to 26.0%. Since the Co content is at least 1%, preferably at least 4%, this means that usually at least one element selected from Si, Mn, Cu, W, V, Nb, Zr, Ta, Cr, C, Al, Y and B must be added (within the range recommended in the rest of the invention), which is related to the fact that Mo is never higher than 12% (for economic reasons compared to those limiting the Co content) and preferably never higher than 7%.
[0149] For the above total amount, the lower limit of 14.0% is justified by obtaining a sufficient hardening effect. Above 29.0%, the magnetic properties of the material as well as the application and use conditions change significantly. Preferably, the lower limit is 15.0%, more preferably 17.0%, in order to obtain conventional values for the most demanding applications envisaged while maintaining an economical steel grade.
[0150] The contents of Ni, Co, and Mo also depend on each other, among which:
[0151] Ni improves ductility (especially at low temperatures) and can control expansion and elastic modulus; Ni also has an effect on toughness and Re / Rm ratio; Ni content is limited by: the lower limit is set to benefit from the favorable properties cited (usually 5% or more of the alloy), and the upper limit is set so as not to hinder the martensitic transformation brought about by its gammagenic nature; for this effect, the influence of Co and Mo must also be taken into account;
[0152] The purpose of adding Mo is to perform structural hardening by precipitation of intermetallic compounds; and, in order to achieve the fracture properties of maraging steel grades, it is necessary to have an aged martensitic structure; Mo precipitates in the hardening as described above (1% or more) and participates in the structural hardening together with the recommended elements (such as Nb); Mo also participates in the nitriding treatment of the surface through its affinity with nitrogen (several percent or more); finally, Mo only limits the formation of weakening phases (Laves phase, σ, μ, θ, δ, etc.), which may be related to local segregation, and its upper limit is 12.0%.
[0153] Finally, with regard to the formation of the aged martensitic structure, the elements Co and Mo act together on the precipitation of the hardening phase, but act independently on the stabilization of the ferrite structure. In order to unify these tendencies, the following formula is proposed to preferably ensure that the Ms temperature is above room temperature:
[0154] 21.5%≤Ni+Co+Mo≤47.5%, preferably 25.0%≤Ni+Co+Mo≤40.0%.
[0155] The Al content is trace to 4.0%, preferably trace to 2.0%. The addition of Al is not necessary, but it is an element that can be used to compensate for the low Co content (related to mechanical properties). The level of Al presence can be reduced to the residual element that must be added in the production process for the initial deoxidation of the liquid metal, or Al intentionally added to obtain specific properties. For a moderate cost, it increases resilience and can participate in structural hardening. In addition, it limits oxidation during the preparation of liquid metal and processing of solidified metal. However, in order not to reduce fatigue strength and toughness, the formation of significant size inclusions (nitride or oxide type containing aluminum) during heat treatment must be avoided. This risk can be limited by limiting the presence of Al to a preferred content of less than 2.0%. In any case, the significant presence of Al must correspond to rigorous preparation conditions, thereby mainly avoiding reoxidation of the liquid metal and strengthening the decantation and capture of any alumina inclusion clusters in the slag originating from deoxidation and reoxidation.
[0156] Like Ti, aluminum promotes nitriding, but it is not easy to control the phases formed. Therefore, precipitates of uncontrollable size can be formed in the different steps of producing liquid steel and in the hot working of solidified semi-finished products, and they have a significant influence on fatigue properties.
[0157] Therefore, the Ti content is trace ~ 0.1%. By avoiding the presence of significant Ti (which is required for other maraging steels, contrary to the present invention), this is to prevent the formation of Ti nitrides during solidification of the liquid metal that deteriorate the fatigue strength of the final product. In the present invention, the desired structural hardening is obtained by other means.
[0158] N contents of up to 0.010% may be necessary for the presence of nitridable additive elements (Al, Ti type) at low levels in order to prevent the formation of nitrides in the liquid phase as much as possible. Apart from these cases, or if most of the harmful nitrides can indeed be removed by decantation during preparation and casting, the permissible N content of not more than 0.010% usually results simply from the quality of the raw materials, the production process and the liquid metal casting.
[0159] The Si content is trace amounts to 4.0%. It is used for deoxidation of the liquid metal during the manufacturing process and is among those elements that can be used to compensate for the relatively low Co content. Even in the presence of Al, the presence of Si may still help capture some of the dissolved oxygen, so that less dissolved oxygen is used to form harmful large clusters of alumina. However, the formation of Si-containing oxides must be avoided in the final solidified steel, so the preferred upper limit of Si is 2.0%. Si increases the solubility of some elements and thereby homogenizes the structure. Finally, it improves the yield strength. A relatively high maximum Si content is acceptable, as long as the necessary provisions are taken during production and casting to obtain an inclusion population that conforms to the present invention.
[0160] The Mn content is trace to 13.0%, preferably trace to 4.0%, more preferably 0.04% to 4.0%. Since Mn increases the solubility of nitrogen in the solid phase, it improves nitriding. Mn also captures free sulfur and thus limits weakening during hot working. In addition, Mn is an effective deoxidizer and can synergize with Si in this respect, and the part of the dissolved oxygen captured by Mn and Si and Cr (see further below) can distribute the dissolved oxygen between elements other than Al, thereby limiting the risk of forming large clusters of alumina inclusions. However, its content is preferably limited to 4.0% to prevent the formation of phases that are not conducive to mechanical properties and to prevent a sharp increase in the proportion of austenite. Mn promotes the stability of two-phase ferrite-austenitic steels (containing less than 70% martensite) that require adjusted properties. In this case, since its proportion must be finely adjusted, the conditions of heat treatment and mechanical deformation must be adjusted to obtain a fine control of the resulting phase transformation and properties. A content exceeding 13.0% may result in the formation of a high Mn content, large-sized inclusions or phases, and a large proportion of austenite which may deteriorate mechanical properties.
[0161] A minimum amount of 0.14% is preferred to thereby obtain significant benefits from the advantages of Mn described above.
[0162] Preferably, and independently of the preferred conditions set for Si and Mn, the sum of Si+Mn is at least 0.13%. In this preference, it is firstly ensured that a significant amount of at least one deoxidizing element can be present in addition to Al, this other deoxidizer (such as Cr) helps to limit the amount of O trapped by Al, wherein Al trapping O has the risk of forming large clusters of aluminum oxide; secondly, Si and Mn belong to the hardening elements preferably added according to the invention to partially replace Co and Mo, and because of their low cost and the lack of harmful side effects within a limited range, they are both (especially when used together) a means of achieving a highly economical benefit of the target structural hardening.
[0163] The C content is trace to 0.03%. For the steel grades of the present invention, elements that produce carbides, such as Nb, have been added, and in the absence of chromium, the carbon content is preferably 0.007% or less. In this manner, soft martensite is formed because carbon martensite is brittle and cannot be formed as required for the product. Since some of these hardening elements that replace Co tend to promote the precipitation of carbides, it is also necessary to prevent the formation of large carbides that deteriorate mechanical properties. Therefore, a controlled C carbon content in the specified range is required or preferred.
[0164] The S content is trace amounts to 0.0020%, preferably trace amounts to 0.0010%, to avoid the formation of sulfides, which, if present in large amounts, would reduce fatigue strength. In addition, S weakens the grain boundaries by segregating at the grain boundaries, so that the steel may form cracks when subjected to stress. Therefore, the presence of dissolved S must be prevented by careful selection of the raw materials and / or deeply desulfurized liquid metal. The exact maximum content allowed (as described above, within the range of up to 0.002%) is adjusted in a known manner according to the target application.
[0165] The P content is a trace amount to 0.005%, preferably less, to limit the possibility of its segregation at the grain boundaries like S.
[0166] B may be present only in trace amounts, but is preferably added voluntarily up to 0.01%. This element promotes refinement of the structure and reduces the grain size. It has a positive effect on the mechanical properties, but it should not be added so much that ductility is reduced.
[0167] The H content is limited to 5 ppm to avoid hydrogen attenuation problems. Performing one or more vacuum treatments during the preparation of the liquid metal and avoiding subsequent contamination of the liquid metal by ambient humidity, slag or any added materials usually allows this level to be observed.
[0168] The permissible content of O will technically depend on the application envisaged for the final product, as will S, B, N and other residues or elements capable of forming precipitates. The maximum content is set at 0.030% (300ppm), due to the methods commonly used to prepare liquid metals. Therefore, the goal is to have oxides in the final product whose composition, distribution and size cannot be controlled. For this purpose, the addition of Al and other oxidizable elements within the limits of the present invention contributes to obtaining a low O content (e.g., 16ppm or less) and avoiding the presence of large oxides, provided that the quality of the production is well controlled and that the atmosphere and refractory materials are avoided as much as possible to reoxidize the liquid metal.
[0169] The Cr content is trace to 5.0%, preferably 0.01% to 5.0%, more preferably 0.1% to 5.0%. Therefore, its presence is not absolutely mandatory, but it has the advantages of improving oxidation resistance, increasing mechanical properties and assisting nitriding. On the other hand, Cr, like Mn, is a γ source element that expands the temperature stability range of austenite by separating the As / Af and Ms / Mf transformation points. Since it is desirable to avoid a significant accumulation of this effect, an upper limit of 5% is reasonable.
[0170] Cr also has a beneficial effect on the properties of the nitrided layer that may form on products made from the steel of the invention: it reduces its tendency to crack. This effect is increased in the presence of significant amounts of Mn.
[0171] Preferably, the sum of Al+Cr is at least 0.1%, preferably at least 0.17%, so that the oxygen forming the oxide can be distributed between Al and Cr, thereby limiting the risk of forming large inclusions.
[0172] Cu content is trace to 4%. It is an element that can be added voluntarily and cannot be considered as an impurity simply and passively to offset the low Co content. If added, its addition must be limited because Cu is γ-sourced and reduces martensite aging. When added in controlled proportions, Cu participates in hardening (together with Mo) and improves oxidation resistance.
[0173] W content ranges from traces to 6.0%. Therefore, its presence is not mandatory and is mainly added when low Co content or even Mo content as mentioned above is required, thereby contributing to structural hardening.
[0174] Zr content is trace to 4.0%. It is an element that may need to be added to help deoxidation, and also to help form fine nitrides so that N does not form too large nitrides if elements that may produce large nitrides (especially Al, since Ti is avoided in large quantities in all cases) are present in very significant amounts. Zr is also included among the hardening elements that can replace Mo and Co.
[0175] Ca and Mg can be found in the metal in the form of oxides or sulphides, as a result of the wear of refractory materials and steelmaking products. It is also advisable to actively add these elements, thereby assisting in deoxidation and controlling the composition of the oxide inclusions, thereby determining their tendency, in particular with Al and Si, to form oxides capable of agglomerating and decanting more easily than inclusions of pure alumina, and to render any inclusions that may still be present in the forming step ductile, thereby reducing their harmfulness. The final content of Ca must be limited to 0.1% and that of Mg to 0.8% to prevent the formation of oxides, the size and distribution of which cannot be controlled.
[0176] Y, Nb, Ta and V may be added up to 4.0% each. They are hardening elements that can be used to compensate for the low Co and Mo contents.
[0177] In addition, Ta and Y contribute to the formation of small-sized oxides, and Nb and V promote the formation of small carbides. Therefore, these elements contribute to the realization of the features of the present invention regarding the control of inclusion size. Nb also has a beneficial effect on the elastic return of the nitrided layer (under low loads).
[0178] Finally, preferably, traces ≤ Al+Si+Cu+Nb+Mn+V+Ta+Cr+W+C+B+Y+Zr+Ti+N≤14.0%, more preferably traces ≤ Al+Si+Cu+Nb+Mn+V+Ta+Cr+W+C+B+Y+Zr+Ti+N≤8.0%, and even more preferably 0.14%≤Al+Si+Cu+Nb+Mn+V+Ta+Cr+W+C+B+Y+Zr+Ti+N≤8.0%. By limiting the value of the sum of these contents, it is sought not to exaggerate the hardening effect brought about by the substitution of these elements for Co and Mo, as well as their secondary influence on other properties of the steel. For this sum, a minimum value of at least 0.14% corresponds to the amount required when it is intentionally desired to replace Co and Mo with at least one of these hardening elements.
[0179] It should be understood that for some elements or for some element contents, the contents defined as "preferred" are independent of each other. Without departing from the invention, one or more of the preferred conditions may be observed without paying attention to other conditions.
[0180] Among these preferred conditions, those most recommended are those with respect to the sum of the contents Al+Cr≥0.17% and Si+Mn≥0.13%. Note that at least one of these two conditions proves to be particularly advantageous for the optimization of the desired results in terms of control of inclusions, mechanical properties and nitriding capability associated with a good behavior of the nitrided layer in the final product when in use.
[0181] Unreferenced elements are present at most only as manufactured impurities and are not added voluntarily.
[0182] Regarding the inclusion group, the criteria to be considered in the present invention are: 2 Polished surface and in the form of cold rolled steel plates 800mm 2 The inclusion group observed by image analysis of the polished surface does not contain non-metallic inclusions with an equivalent diameter greater than 10 μm, and preferably does not contain non-metallic inclusions with a size greater than 8 μm.
[0183] For hot-processed parts or plates, for example, at 650mm2 SEM image analysis of the polished surface for at least 200 mm 2 It is observed that the population optimally contains no more than 2, and preferably no more than 1.5, non-metallic inclusions having an equivalent diameter greater than 1.5 μm per square millimeter of the hot worked plate.
[0184] The non-metallic inclusions considered are oxides, sulfides and nitrides. The population of oxides is controlled primarily by the choice of the production method (after intensive deoxidation of the liquid metal, large inclusions are removed as carefully as possible, in particular using a remelting process of the electrode originally cast from the liquid metal). The population of sulfides is controlled by using very low S contents, which requires careful selection of the raw materials and / or desulfurization of the liquid metal. The population of nitrides is controlled by using low or very low N contents, for example by carrying out the preparation of the liquid metal and the remelting of the electrode under reduced pressure, and by limiting the Ti content of the metal.
[0185] The steel of the present invention is prepared by the following route, for example but not limited thereto.
[0186] In order to adjust the basic composition of the steel composition, liquid steel is first produced in an electric arc furnace and optionally also in a ladle furnace and then cast in the form of remelting electrodes. These electrodes are:
[0187] Either, after casting and solidification of the liquid steel, a primary remelting is carried out under vacuum (VIM process: vacuum induction melting; or VAR process: vacuum arc remelting known per se) or by electroslag remelting (ESR process, known per se) to form ingots, billets or slabs;
[0188] Either, after casting and solidification of the liquid steel, it is remelted several times under vacuum (VAR process: vacuum arc remelting) or by electroslag remelting (ESR) to form ingots or slabs.
[0189] Therefore, after preparation and casting into electrode form, a single remelting of the electrode or multiple remelting of the electrode, such as VAR+VAR or ESR+VAR, is performed. These remeltings purify the metal and improve the quality of solidification by reducing segregation and refining the solidification structure. In particular, ESR remelting can effectively reduce the sulfur content, and VAR remelting can effectively reduce the nitrogen content.
[0190] Then, after heating to 1050° C. to 1300° C. (generally about 1200° C.), the ingot or slab is hot rolled to obtain a hot rolled sheet or strip having a thickness of several millimeters (e.g. about 1.5 mm to 5 mm thick). For steel grades having, for example, a content of gamma-source elements exceeding 10%, it may be appropriate to control the cooling of the sheet in order to promote the formation of martensite and prevent the continued presence of what would prove to be an excessively high amount of austenite. This is particularly the case with steels containing Mn. By experimentation, the person skilled in the art will be able to determine whether such controlled cooling is helpful for the steel whose specific conditions it is desired to obtain with the existing method.
[0191] Hot rolled products of this thickness can be used in the hot rolled state in some cases, or they can be hot formed, or they can be used in a controlled recrystallized state. After hot rolling and spool winding (equivalent to real heat treatment) of the strip, recrystallization may have reached a sufficient degree, but if it is not sufficient to obtain the desired microstructure and / or mechanical properties, a recrystallization annealing can be subsequently performed to adjust the structure. In the latter case, a person skilled in the art is able to adjust the recrystallization annealing parameters (temperature, time, etc.) to adjust the microstructure (especially grain size) and the desired mechanical properties.
[0192] Typically, after hot rolling and optional recrystallization (see other types of heat treatment), the target Vickers hardness value is 285 Hv10 or higher. This indicates a tensile strength of 950 MPa or higher and a uniform elongation of 5% or higher.
[0193] The hardness is evaluated on the cross section of the hot plate. According to the ASTM E112 standard, the target structure of hot rolled pickled products is a fine structure with an austenite grain size number of 10 or more, it being understood that the higher the number given for the grain size, the finer the grain size.
[0194] It is also possible that these hot rolled strips, optionally heat treated, are not used directly, but that their thickness is subsequently reduced by cold forming for the envisaged application. In this case, they are pickled and subsequently cold rolled (with one or more intermediate annealing operations between the different cold rolling passes), and optionally one or final annealing operation for aging, recrystallization annealing, or other types of heat treatment processes or appropriate surface treatments based on the target application (described in detail later) to obtain cold rolled strips with a thickness of less than 2 mm, preferably 1 mm or less, for example 0.4 mm or 0.2 mm.
[0195] The recrystallization treatment of the cold-rolled strip is preferably carried out at a thickness such that the cold-rolled strip has a strain hardening rate greater than 30%, more preferably greater than 40% during this treatment, thereby providing the strip with a grain size preferably of ASTM 10 (average grain diameter below 10 μm) or finer (according to standard ASTM E112).
[0196] Annealing treatments for obtaining a fine grain and / or stress relaxation and / or normalization of the metal are carried out in a protective atmosphere by appropriately adjusting the parameters of temperature and time. These parameters depend on the specific conditions under which the heat treatment is carried out and can be determined by a person skilled in the art in each specific case.
[0197] The preferred requirements regarding the grain size of the cold-rolled product with optional heat treatment also apply to the product used in the hot-rolled state after optional heat treatment.
[0198] To improve the flatness of the strip and, if necessary, to improve the martensitic transformation, the strip may also be subjected to a light final skin-pass with a reduction of 1% to 20%.
[0199] Generally, the hardening (aging) treatment of the cold-rolled strip is preferably carried out at a thickness such that the cold-rolled strip has a strain hardening rate of more than 30%, more preferably more than 40% during the treatment.
[0200] The parts can then be cut from the strip and shaped, for example by folding, welding, etc., and hardened at between 400°C and 600°C for 30 minutes to 5 hours, preferably at 420°C to 550°C for 30 minutes to 2 hours, for example at 420°C for 30 minutes, or at 480°C for 2 hours.
[0201] The hot rolled product can also be subjected to a typical maraging steel hardening treatment, with the usual expected benefits to mechanical properties from said treatment.
[0202] According to the invention, the product derived from a steel grade with at least 70% martensitic, cold rolled and optionally heat treated, is capable of reaching a tensile strength value Rm of at least 2030 MPa, a supplementary yield strength Rp of at least 2000 MPa. 0.2 , and an elongation A of at least 1% (5,65) On the other hand, products derived from two-phase ferrite-austenite grades have less mechanical properties after certain thermal cycles, but retain improved properties under dynamic stresses in service (strain hardening, strengthening phase transformations and nitriding).
[0203] Optimally, these properties can be achieved on hot rolled products that have undergone appropriate heat treatment.
[0204] The products can then be surface hardened (by nitriding, carburizing, carbonitriding, shot peening, etc.) to improve their fatigue properties. Typically, the surface hardness HV0.1 can be at least 950 without the need for nitriding methods and conditions other than those standard methods and conditions known in the art.
[0205] The experiments were carried out on reference samples (denoted Ref) and steel samples according to the invention (denoted Inv), and their compositions are summarized in Table 1, expressed in wt%. The remainder is iron and manufacturing impurities that are not important for the properties under consideration. The symbol "-" indicates that the element is present in the sample only in trace amounts or very small amounts and has no metallurgical effect.
[0206]
[0207]
[0208]
[0209]
[0210]
[0211] Table 1: Composition of test samples
[0212] The steel of the present invention and the reference steel (samples used in Table 1) were prepared according to the following protocol to obtain strips having a thickness of 0.4 mm.
[0213] The samples of the invention were prepared in a laboratory investigating a vacuum induction furnace, the weight of the test castings being several kilograms (5 to 50 kg), with the exception of samples Inv 13, Inv 18, Inv 19, Inv 24, Inv 54, Inv 5, Inv 60 and Inv 61 which were first melted in an electric arc furnace and then prepared on an industrial plant (several tons) by applying the VIM and remelting VAR processes.
[0214] Samples Ref 1, Ref 2 and Ref 4 were prepared on industrial equipment. Other reference samples Ref3, Ref 5, Ref 6, Ref 25, Ref 26, Ref 50, Ref 51 were prepared in the laboratory under the same conditions as the laboratory-prepared samples of the present invention.
[0215] The structures and inclusion groups evaluated on the laboratory castings are very close to those obtained on industrial equipment, with similar production times. The differences in density and size of the finest inclusions do not exceed 20% of the benefit of the laboratory castings (considering the ingot form used), everything else remaining constant. However, the castings studied are characterized by the absence of remelting, which offsets the differences in the aforementioned parameters and makes the laboratory test results reasonably comparable to those of the industrial tests. The ingots are then transformed into slabs by blooming to reduce the thickness, which is between 100 mm and 200 mm.
[0216] Then, after heating to about 1300°C, the slab is hot rolled to a thickness of 3.5 mm, which means hot rolling at a temperature of 1285°C, taking into account the transfer time between the furnace and the rolling mill. Subsequently, the metal is pickled and cold rolled to a thickness of 0.4 mm or less. Sometimes, in different steps of the production process, an austenitizing or solution annealing operation is carried out, followed by recrystallization and then aging annealing, which are respectively carried out at 800°C to 850°C (no more than 1 hour), at 850°C to 1200°C (duration less than 10 minutes), at 420°C to 550°C (30 minutes to 4 hours).
[0217] Table 2 shows:
[0218] After hot rolling, the plate width of each sample in Table 1 is 650 mm in the middle. 2 The size of the largest inclusions observed in these samples;
[0219] Under optical microscope (OM), at 650 mm 2 Evaluation of inclusion density on the surface for inclusions larger than 4 μm;
[0220] and, the inclusion density observed under a scanning electron microscope (SEM) by automated image analysis on industrially prepared samples, which involved 2 ~400mm 2 Inclusions larger than 1.5 μm were observed on the surface.
[0221] The largest dimension of the observed particle is recorded as the inclusion equivalent diameter (denoted as "Dcircular"). It should be understood that the "diameter" of an inclusion refers to the "equivalent diameter", i.e., the "diameter" of an inclusion if it had a circular cross-section and had the same surface area as the observed inclusion if the observed inclusion had a cross-section more complex than a simple circle.
[0222] Furthermore, since optical image analysis can only distinguish color contrast and not the composition of inclusions, only the absence of TiN (which, according to the technician’s experience, has an orange contrast) and the inclusion density of various other inclusions with a size greater than 4 μm in the evaluation particles could be verified under the optical microscope. Finally, the 200 mm 2 ~400mm 2 (Magnifications ×300, ×1000, ×10 000, respectively) A more precise characterization of the inclusion population was performed by counting and automatic analysis and an evaluation of their surface density. Thus, the density and type of inclusions in industrially prepared samples were determined on 3.5 mm thick hot rolled strip. All densities were adjusted to the surface density (per mm 2 of inclusions).
[0223]
[0224]
[0225] Table 2: Size of the largest inclusion and inclusion density observed on hot rolled samples under optical microscopy (for inclusions larger than 4 μm), and inclusion density observed under scanning electron microscopy (for inclusions larger than 1.5 μm)
[0226] These results show that, for the samples of the invention, by adjusting the composition of the material and the production method, it is possible to obtain a small inclusion density and a complete absence of relatively large-sized inclusions, i.e. no inclusions larger than 10 μm on the hot-rolled product, and optimally an inclusion density similar to or lower than that in the reference samples. In reference sample 1 there are also no such inclusions, but the number of small oxide inclusions (5 μm to 10 μm in diameter) is significantly higher than, for example, the industrial samples of the invention, which is detrimental to the fatigue properties. As for reference sample 2, it has an excessively high nitride density, including nitrides larger than 10 μm in size. This characteristic itself is the main obstacle to achieving sufficient fatigue strength (due to the size, type and morphology of the nitrides), and it is considered unnecessary to detect the oxides of this sample.
[0227] Therefore, the sample of the present invention contains only small diameter and low number of inclusions (it is necessary to count the inclusions of smaller size under a scanning electron microscope to evaluate the number of representative inclusions that can be detected by the resolution of the equipment and obtain an accurate estimate of the size exceeding 1.5 μm). In particular, there is no Ti nitride, which is particularly related to the absence of Ti and the very low content of N. This situation is the same as that of reference sample 1, although the inclusion density and the diameter of its largest inclusion are slightly higher than the optimal case of the present invention. For reference sample 2, it is confirmed that nitrides (mainly Ti nitrides) dominate therein and exist in the form of inclusions with almost no toughness and generally have too large a size to achieve the purpose of excellent fatigue strength.
[0228] Similarly, Ref 4 and Ref 5 having increased S content and Ref 3 and Ref 6 having high contents of Al and Y respectively contain large-sized (greater than 10 μm) oxide inclusions in the hot rolled products.
[0229] Inclusion counting under optical microscopy was first performed (for speed and ease of implementation), however due to the small size of the inclusions and their low number, their limits are quickly reached. Moreover, if the counted images are not properly classified by the experimental observer, the use of optical microscopy in the present invention for inclusions of oxides, sulfides or other types of particles introduces artifacts due to confusion between gray shades caused by sample preparation, surface contamination, etc. Therefore, automated inclusion counting and analysis using SEM and EDX is preferred to obtain a more reliable representation of the surface density of inclusions in industrial samples produced according to the present invention.
[0230] It is thus determined that the inclusions of the samples of the present invention have a lower maximum size than the reference sample 1 (not containing Ti), and most of the samples of the present invention further exhibit an inclusion density evaluated under a scanning electron microscope that is lower than the inclusion density of the reference sample (evaluated under the same conditions). Thus, the density of inclusions with a diameter greater than 1.5 μm under SEM observation is low, more than twice lower than that of the reference sample 1, and the size of the largest particle observed on the industrial casting is smaller (about 1 μm smaller) than that observed in the reference sample.
[0231] From Table 2, the optimum composition range specific to the inclusion group of the steel of the present invention can be obtained.
[0232] The inventive samples Inv 9 to Inv 13 show that up to 4% Cu (when the production process is controlled and the remaining elements according to the invention are present), the maximum size of the inclusions appears to be controlled.
[0233] On the other hand, samples Inv 14 to Inv 19 show a preferred composition with a Nb content of 2% or less, and within this composition range, the carbon content is less than 0.007% to prevent the formation of carbides with a size greater than 10 μm, or other carbide-forming elements such as Cr are preferably added (a higher carbon content is allowed in the presence of Nb).
[0234] Samples Inv 20 to Inv 24 show that the manganese content is 4% or less in order not to promote the formation of inclusions with a size greater than 10 μm, and above this content, the proportion of free carbon (preferably below 10 ppm) needs to be carefully controlled.
[0235] The samples with low Co (wherein aluminium and optionally silicon and / or chromium are added) Ref 25, Ref 26, Inv 27 to Inv 34, Inv 39 to Inv 49, Inv 52, Inv 53, Inv 56 to 59, Inv 61, Ref 50 and Ref 51 have inclusions with a diameter of 10 μm or less (even 8 μm or less), in particular with associated oxygen contents below 16 ppm.
[0236] It is known to the person skilled in the art that cold working may only reduce the size of the inclusions by their number, but will not in any case increase the size of the inclusions.
[0237] The steel grades of the invention have the following advantages due to their inherent chemical composition: they do not form nitrides during production and the size and type of residual inclusions, in particular oxides, can be controlled. By carefully controlling the raw materials used and the processes adopted to produce low contents of residual elements N, S, C and P, and by deoxidation of the liquid metal, oxide particles of limited size (10 μm or less, preferably less than 8 μm) and with the right composition obtained within the processing range are formed. Depending on the composition of the steel, the aluminum oxides formed are, for example, mixed oxides of Al and Mg (this element inevitably comes from the slag and the refractory materials of the production equipment) or aluminum oxide alone, but also Si oxides, Ca oxides, Mg oxides or other mixed oxides are formed; sometimes, small amounts of fine sulfides or carbides strengthen these inclusion groups.
[0238] The important mechanical properties of the various samples are summarized in Tables 3, 4 and 5, where Table 3 relates to the samples in the hot-rolled stage, Table 4 relates to all the samples in the hot-rolled condition after an aging annealing to induce precipitation hardening, and Table 5 characterizes all the samples in the cold-rolled and aged condition (where the reference treatment is 3 h at 480° C.). These properties are measured in the longitudinal direction relative to the rolling direction of the strip. These properties are the Vickers HV 10 hardness (for the hot-rolled samples), the ultimate mechanical tensile strength Rm (expressed in MPa) for the aged hot-rolled samples, the compensated yield strength Rp 0.2 (expressed in MPa), the uniform elongation Ar (expressed in % and measured on a test piece of length L0, equal to 5.65 times the square root of the initial cross-section S0) for cold rolled samples in the aged and unaged state.
[0239]
[0240]
[0241] Table 3: Vickers hardness of the prepared samples in hot rolled state Hv 10
[0242]
[0243]
[0244] Table 4: Tensile strength Rm of samples in hot-rolled and aged state
[0245]
[0246] Table 5: Mechanical properties of samples in the cold rolled condition after rolling and in the cold rolled and aged condition
[0247] The mechanical properties obtained by the samples according to the invention in the aged hot-rolled and / or cold-rolled state are similar to or even improved on those of the reference samples. Thus, the steel grade according to the invention combines economic attractiveness (reduced material costs by reducing the costs of Ti, Co, etc.) with high mechanical properties. For each of the alloying elements Nb, Cu, Mn, W, Ta, V, an ultimate tensile strength higher than 1950 MPa in the aged state can be obtained by adjusting the composition and the implementation method.
[0248] Table 4 shows the values of Rm>2000 MPa in the hot rolled state for the added elements with adjusted contents, so that a martensitic structure capable of being aged can be obtained (e.g., as shown by samples Inv 14 to Inv 19, Nb shows interesting hardenability, on the other hand, the manganese content is 4% or less and / or the added Cr content is controlled to prevent the formation of austenite predominantly, etc.). In addition, the inventive steel grades Inv 27 to 49, Inv 52 and Inv 61 suggest: Co+Mo content higher than 9%, preferably higher than 15% to achieve mechanical properties at least equivalent to those of reference samples 1 and 3 in the aged state.
[0249] The compromise between these mechanical properties combined with a controlled inclusion population by carefully determining the processing conditions has demonstrated the novelty of the present invention, with the material having improved surface properties in applications subject to fatigue stresses after nitriding.
[0250] Tests were performed on hot-rolled and cold-rolled products to obtain the optimum aging conditions (after normalization or solution annealing).
[0251] Each steel grade was previously solution annealed at 850°C for 1 hour in a reducing atmosphere to provide a homogeneous structure. Experiments were conducted on these annealed materials for different (time-temperature) pairs of conditions to determine the aging conditions suitable for the target application and the steel grade produced.
[0252] Depending on the aging conditions tested, the optimum value is determined based on the hardness after aging and the phases present at 420°C to 550°C in argon.
[0253] Steels Inv 1 to Inv 4 containing V show the same aging conditions as those conventionally used in Reference Samples 1 and 2 (e.g., treatment between 450°C and 500°C for ≤3h), and are able to obtain Rm values above 1900 MPa in the aged state for V contents ≤4%; Steels Inv 5 to Inv 8 containing Ta show increased mechanical properties (Rm>1940 MPa) after adding 0.5% or more Ta under similar aging conditions. Steels Inv 9 to Inv 13 containing Cu show the best aging conditions in the region of 500°C for ≤2h (or 480°C for 3h), and are able to obtain Rm values above 1940 MPa in the aged state after adding 2% Cu; These aging property levels increase in the presence of Cr (<2%) and Mn (<1%) and structural hardening (i.e., Co+Mo+Cu+Cr+Mn<25%). The Nb-containing steel grades Inv 14 to Inv 19 show mechanical properties after aging that are superior to those of reference sample 2, with a wide range of aging conditions from 420°C to 550°C for 30 minutes to 5 hours, provided that a small proportion of Nb is added. The recommended optimum treatment is 450°C to 500°C for 2 hours.
[0254] Adding controlled proportions of Cr and Mn increases age hardening. However, these steel grades require control of the Nb content to prevent the formation of inclusion clusters or particles with a size greater than the maximum value defined in the present invention. Therefore, the Nb content is mandatory ≤ 4%.
[0255] Steel grades Inv 20 to Inv 24 and Ref 25 and Ref 26 containing significant amounts of Mn (more than 0.19%) form steel grades that can be dual phase, requiring a mostly martensitic structure to be obtained for optimal aging. Therefore, steel grades with relatively limited Mn content (traces ≤ Mn ≤ 4%) can achieve values of Rm>1940 MPa, wherein the aging conditions used are the same as conventionally used in Reference Samples 1 and 2 (e.g. treatment at 450°C to 500°C for ≤3 hours). At these controlled proportions of Mn, controlled additions of Al, Si or Cr can increase age hardening, provided that the martensitic structure is maintained before aging.
[0256] Since the Mn content of steel grades Ref 25 and Ref 26 exceeds 13.0%, they are outside the scope of the present invention. As shown in Table 2, although they are within the acceptable range with respect to the maximum inclusion size: the equivalent diameter of the maximum inclusion is 10 μm, the 1.73 and 1.75 inclusions / mm 2The inclusion density of is the highest for this size class, so their inclusion population is not optimal. Table 4 shows that their Rm values in the hot rolled and aged conditions are significantly lower (489 MPa and 544 MPa).
[0257] As in the reference steel, in the steel of the invention, the mechanical properties of the maraging steel are based on age hardening caused by Co and Mo (and other added elements). Therefore, low contents of Co (typically Co <5%) and / or Mo (typically Mo <5%) do not allow Rm values exceeding 1530 MPa to be obtained after aging. The use of higher proportions of Co (5% to 16%) or Mo (3% to 9%) provides the realization of higher levels of mechanical properties (tensile strength, fatigue resistance, etc.). These trends are confirmed by characterizing samples Inv 39 to Inv49 (with Co contents ranging from 2% to 7%), which show that the addition of Al, Si or Cr cannot compensate for Rm, which involves the contents of Co = 1.0% to 10.0% and Mo = about 5%; after aging, the ultimate tensile strength Rm cannot exceed 1800 MPa, regardless of the addition of up to 1% Al, up to 0.13% Si, up to 0.1% Ti, or up to 0.5% Cr.
[0258] The object of the invention is to adjust the mechanical properties imparted to a given base metal by means of an initial content of the elements Co and Mo selected according to the target properties, without degrading the inclusion population and fatigue behavior of the material and at low cost. In many embodiments of the invention, after aging, tensile strength Rm values higher than 1900 MPa are targeted and obtained, in addition with defined inclusions of controlled size, thus ensuring in particular good fatigue behavior. As regards other objectives in terms of durability and mechanical properties, in different variants of the invention, they can be considered and obtained by adjusting the content of elements, in particular Co, Mo, W, Cu, V, Nb, Mn, Si, Al, Cr.
[0259] For example, the steel grades Inv 27 to Inv 38 containing relatively large amounts of W and Al, wherein the W content is preferably higher than 0.8% and the Co content is higher than 10%, can exhibit higher mechanical properties than Ref2 after aging. Such properties after aging increase with the addition of Al or Cr and structural hardening. Typically, the same aging conditions as those usually used for steel grades Ref 1 and Ref2 enable Rm values higher than 1940 MPa to be obtained in the compositions of Inv 37 and Inv 38 in the aged state.
[0260] It should be noted that grades Inv 48 and Inv 49 have Ti contents close to the acceptable limit (0.109%), which for rounding and normal analytical precision can be considered equivalent to 0.1%. They are not among the top of the best Rm values, and Inv 48 has a maximum equivalent inclusion diameter close to the acceptable range, and the inclusion density is not optimal. These grades show that care must be taken to keep the 0.1% limit for Ti within the scope of the invention.
[0261] Steel grades Ref 50 and Ref 51 have S contents (0.004% and 0.0053%) exceeding the permissible limit (0.002%). Therefore, their inclusion population is not optimal. Ref 50 has a maximum inclusion equivalent diameter of 10 μm, thus close to the permissible value, and an inclusion density of 0.81 inclusions / mm 2 , relatively average. Ref 51 has smaller inclusions, but more in number. Their Rm values in the hot rolled and aged condition are 1700-1800MPa, which is not optimal. Due to these S contents which are a bit too high, the resulting grain boundary weakening makes hot working more difficult than expected.
[0262] Inv 52 and Inv 53 are comparable to Ref 50 and Ref 51, except that the S content is lower and in accordance with the invention. Therefore, they have improved Rm in the hot rolled and aged condition and have better fatigue resistance and better hot workability.
[0263] Inv 54 and Inv 55 are characterized by their high Mo content (about 9.9% and 11.8%). They have excellent mechanical properties. The content of C, Al or Cr slightly higher than that of other examples of the invention provides an acceptable quality / price ratio, even if not optimal. These examples illustrate the influence of Mo on mechanical properties, but they only partially meet the economic goals set by the invention.
[0264] Inv 56 represents a steel grade with a high Al content. Cr is added to Inv 57, and non-negligible amounts of Cr and Zr are added to Inv 58. With the above added elements, these examples show interesting properties that can be optimized with the preferred contents described above.
[0265] Inv 59 has high contents of Si and Y.
[0266] Ref 3 has too high an Al content and therefore contains inclusions that are too large and cannot be removed, making it unsuitable for the target application subject to fatigue stress.
[0267] Ref 4 and Ref 5 contain excessive S, and thus form excessive sulfides, which additionally serve as sites for the generation of oxides, thereby indicating that excessive inclusions exist on the hot-rolled products.
[0268] Ref 6 has an excessive Y content which forms oxide inclusions of excessive size which cannot be removed by depositing liquid metal.
[0269] Inv 60 shows a strong presence of Ca and Inv 61 shows a strong presence of Mg. They show that in the present invention, these two deoxidizers can be used in non-negligible amounts, provided that the skilled person pays attention to the known rules regarding the properties and refining of refractory materials.
[0270] It is worth noting here that the steel grades of the invention are compatible with aging conditions that allow the mechanical properties to be enhanced and that are moreover easy to implement in terms of processing and the associated costs. The stability of the properties obtained (especially hardness) makes it possible to obtain the same or comparable properties obtained with a treatment process of 2 to 5 hours for conventional steel grades by carrying out an annealing operation of a short time (generally 30 minutes). These characteristics of simplicity and economy of heat treatment are particularly favorable to the economical steel grades for the purposes of the invention.
[0271] The novel steel grades of the invention have interesting mechanical properties (hardness, yield strength, fracture strength, etc.) which can be optimized for certain applications with what is known as "infinite" resistance, thus ensuring the ability to withstand strong fatigue stresses. Thus, under these conditions of aging and inclusion population optimization according to the invention, improved properties, such as fatigue properties, at dynamic yield stress can be achieved by subsequent surface treatments (nitriding, carbonitriding, carburizing, shot peening, etc.).
[0272] Finally, the improved properties of these steels according to the invention were also tested after surface compression treatment. Nitriding is carried out before stressing on thinner thickness materials subject to fatigue in order to delay the onset of surface cracking. This compression treatment can be carried out in a known manner by shot peening.
[0273] For the steel grade of the present invention, various nitriding conditions were tested, including treatment at 420° C. to 480° C. for 30 minutes to 90 minutes in a gas atmosphere (cracked NH 3 atmosphere).
[0274] The nitrided layers are then formed by diffusing nitrogen within the various nuclei, to a characteristic thickness of several tens of micrometers (assessed by chemical etching or by depth analysis by glow discharge spectroscopy (GDS)). They sometimes contain fine, evenly distributed precipitates, and their chemistry can be adjusted, if deemed necessary, by adjusting the steel composition and the nitriding conditions.
[0275] Figure 1 The density of the hardened phase obtained on sample Inv.15 characterized by thin-section transmission electron microscopy after nitriding at 420°C for 30 minutes is shown. The hardened precipitates are essentially Mo x Nb y (where x = about 2y) with uniform distribution and size ranging from 80nm to 400nm. Some Nb and Mo carbides were also found, as well as smaller sized nitrides with specific stoichiometry and lattice parameters.
[0276] In the investigated time and temperature ranges, the steel grades of the invention show increased surface properties after nitriding. Table 6 shows the hardness levels evaluated by micro-indentation under the same conditions (average of three Hv 0.1 surface measurements). Various nitriding conditions were investigated under cracked NH3 gas nitriding; these conditions can also be applied to ion nitriding, carbonitriding or others to obtain similar properties.
[0277]
[0278]
[0279] Table 6: Average Hv0-1 hardness values evaluated by micro-indentation of the outermost surface under different nitriding conditions
[0280] It should be understood that the measurement uncertainty of this type of test is high when testing on samples with rough surfaces and local marks. The results in Table 7 must therefore be interpreted in terms of overall trends.
[0281] Therefore, in addition to excellent mechanical properties, controlled material costs and controlled inclusion populations, the samples of the present invention exhibit nitridability that results in increased surface hardness levels and increased frictional resistance compared to reference samples 1 and 2. As a result, it can be expected that the outermost surface hardness level is similar to that of reference samples 1 and 2 (e.g. Hv0.1>900), and even for some steel grades of the present invention, an outermost surface hardness of more than 50 Hv0.1 can be obtained with reduced nitriding time. Therefore, under appropriate nitriding conditions that are not particularly harsh, the steel grades of the present invention can reach an outermost surface hardness level of more than 1000 Hv0.1 (even 1050 Hv0.1).
[0282] However, for certain applications subjected to fatigue stresses, it is advisable not to reach a surface hardness level that is too high (Hv0.1 hardness) relative to the aged core (Hv10 hardness) of the material, in order to prevent weakening of the internal interfaces or the outermost surface. For this purpose, it is better to have a regular nitrogen diffusion profile deep in the material than a sharp diffusion profile that leads to the presence of non-uniform main precipitation areas on the surface. In steels, these areas are called "compound layers" and are formed, for example, by very hard and brittle iron nitrides. In this case, for the samples of the invention, it was verified that there were gas nitriding conditions that prevented the formation of iron nitrides on the outermost surface while maintaining sufficient surface stress to delay cracking initiated under dynamic stresses in use (in the area of the target surface hardness).
[0283] exist Figure 2 The minimum and maximum hardness values (Hv0.1 hardness) of the outermost surface under different nitriding conditions (temperature, time) are given in FIG. It can be seen that for each major family of hardening elements present according to the present invention, an outermost surface hardness level higher than 900 Hv0.1 can be achieved. Therefore, at least the same fatigue surface properties as those of the previously cited reference documents can be obtained.
[0284] It was established that steel grades containing Mn or Cu with quantified Cr additions produced on industrial tools can show increased outermost surface hardness after nitriding compared to the steel grades of the invention without Cr, and similar effects can be expected by adding Al in defined proportions together with hardening elements (such as Ta, see Inv 8).
[0285] Therefore, with sufficient Co and Mo levels to obtain the target mechanical properties detailed above, the present invention shows that for each type of steel, the outermost surface hardness values above 900 HV0.1 may be achieved, which is based on the following basis:
[0286] When the content of hardening elements is below 0.5%, values below 900 Hv0.1 are observed on vanadium-containing steel grades; above this value, increased hardness values are expected on the outermost surface;
[0287] For the steel grades with the inventive tantalum content (Inv 6 to Inv 8 in Table 7), starting from the addition of 3% Ta (with adjusted nitriding conditions), the outermost surface reaches hardness values above 940 Hv0.1;
[0288] The Cu-containing grades also show increased hardness levels (and residual stresses) on the outermost surface starting with the addition of 2% of hardening elements and in the presence of Cr and Mn (Inv 13); these elements promote nitrogen solubility on the surface;
[0289] On the other hand, the steel grades 14 to 18 of the present invention show that a vanadium content below 2% is able to achieve a sufficient hardness level on the outermost surface (without a compound layer);
[0290] The steel grades containing manganese show a good compromise between mechanical properties / inclusion groups, showing an increase in the hardness level of the outermost surface when Cr is present (Inv 24);
[0291] Testing of steel grades containing W and Al (Inv 38 and Ref 51) has not yet been able to determine the nitriding conditions that would allow high hardness levels to be achieved on the outermost surface.
[0292] Finally, it was demonstrated that these achievable high surface hardness values are accompanied by controlled residual stresses (assessed by X-ray diffraction), making it possible to compress the surface relative to the core and thereby delay the initiation of surface cracking.
[0293] Figure 3 A qualitative evaluation of the residual compressive stress on the surface of the nitrided rolled sheet is given for samples Ref 1, Ref 2, and various samples of the present invention. For each sample, the minimum and maximum values of the estimated compressive stress are given for all tests carried out at varying temperatures and nitriding times. The residual stress in the nitrided layer is evaluated on the sample surface by X-ray diffraction with the following parameters: Chi varies between 0° and 51°, measurement interval 1 s, sin 2 (psi) is 0-0.6 per 0.1 pitch. The values obtained under these conditions allow the determination of the stress level on the material surface by monitoring the changes in the position of the Fe wire. It can be seen that the residual stress of the sample of the present invention is improved compared to the residual stress observed on the reference sample 1.
[0294] Therefore, when applying the invention, it is easier to control the properties of the nitrided layer and thus adapt the layer to the specific requirements of the intended use of the future product. If considered to be preferred, it is thus easier to avoid the presence of phases in the nitrided layer, which are usually called "compound layers", on the outermost surface. These phases consist of iron nitrides, in particular Fe4N, Fe2N, Fe2N 1-x Type of precipitation occurs.
[0295] The characterization of the nitrided layers of some samples (reference sample Ref 1 and inventive samples Inv 13, Inv 18, Inv 21 and Inv 24) was done by carrying out a test generally called "scratch test" derived from the "durometer test" and differed by the low load applied.
[0296] For these tests, a spheroconical tip, such as a diamond tip for Rockwell C hardness testing (120° angle, radius of curvature of the tip 100 μm) was passed through the nitrided layer / substrate system, applying a constant substrate travel speed with increasing load at the tip.
[0297] The degradation of the coating under applied load is a combination of elastic and / or plastic indentation stresses, friction stresses and internal residual stresses in the material.
[0298] At low loads, these stresses may be the cause of tensile or compressive cracking of the coating surface, although the coating surface will continue to adhere to the substrate.
[0299] The scratch test is a comparative test that detects the propagation of sound waves through microcracks in the material (if any), detects the indentation depth of the pressing indentation tool (relative to the real surface initially touched), and enables the evaluation of the residual depth of the coating on the indentation channel after the test. The latter estimate enables the evaluation of the resilience of the coating / substrate system or surface / substrate system after the application of increasing low loads.
[0300] On each system, three consecutive measurements were performed at intervals of 1 mm on the surface of the nitrided sample by applying a load increasing from 0.03 N to 10 N on 10 mm of the nitrided surface.
[0301] Although there was little difference in the results for the various samples of the present invention in terms of normal force or indentation depth evaluation, differences were shown in some features of the nitrided layers of the present invention.
[0302] For example, Figure 4 The resilience of the nitrided layer / substrate system after the scratch test is shown for nitrided samples Inv 21 and Inv 24 (treated at 480°C and 450°C in a gas atmosphere for 30 minutes, respectively) by the relative difference between the indentation depth and the residual depth (significantly reduced curves).
[0303] Inv 21 is an example containing Mn (1.970%), where the Cr content (0.007%) comes only from impurities contained in the raw materials used. Inv 24 is an example containing 1.930% Mn, thus a content comparable to that of Inv 21, but with an associated Cr content of 0.902%, thus corresponding to a very significant Cr addition. The two samples give comparable results for the indentation depth during the pressing phase of the scratch test, but for Inv 21 the curve is more irregular than for Inv 24.
[0304] Figure 5Shown are the results of the acoustic emission during the scratch test of the two same nitrided samples Inv 21 and Inv 24. Here the difference is clearly more pronounced, with Inv 21 having a higher emission than Inv 24.
[0305] Therefore, the addition of Mn relative to the addition of Cr shows less noise when evaluating the depth, which is consistent with the significantly reduced acoustic emission in nitrided Inv24 ( Figure 5 ).
[0306] This behavior is also observed in other steel grades containing Cr according to the present invention.
[0307] It follows therefore that the significant presence of Cr reduces the potential for cracking of the nitrided layer of the steel grade according to the invention under low applied loads (<10 N), which is particularly true for fatigue stressed components which are subject to local rubbing, pressing or friction in use.
[0308] Similarly, Figure 6 The elastic behavior of the nitrided layer / substrate assembly after the scratch test of the nitrided samples Inv 13, Inv 18, Inv 21 and Inv 24 is shown in comparison with the sample Ref 1 (average curve of three tests performed for each sample, Inv 33, Inv 18, Inv 21 and Ref 1 were treated at 480°C in a gas atmosphere for 30 minutes, Inv 24 was treated at 450°C for 30 minutes). The curve offset from the X-axis of the residual depth curve illustrates the residual plastic deformation after the test.
[0309] Figure 6 The increased elastic behavior of the nitrided layer of the samples according to the invention is shown compared to the nitrided layer obtained with Ref 1. The resilience, evaluated by the difference between the curves of the indentation depth and the residual depth, is significantly increased for the samples containing Cu (Inv 13, which also contains Cr) or Nb (Inv 18). For these samples, there is a variation with a height of about 15 μm thick, while for the steel grades containing Mn (Inv. 21) and Mn+Cr (Inv 24, which also contains some Si), the height is 13 μm, thus twice that of Ref 1, which does not contain these alloying elements but contains a Co content (16.50%) higher than that of the test sample according to the invention (about 13%). For all these samples, the Mo content is about 5.0% to 5.30%.
[0310] In addition, for the samples Inv 13, Inv 18, Inv 21, Inv 24 of the present invention, the evaluated residual depth rd is smaller and slightly better than that of Ref 1.
[0311] This behavior is indicative of the improved resilience of the nitrided layer of the present invention, which is particularly beneficial in applications where the component is subject to fatigue, as it can reduce plastic deformation of the substrate / nitrided layer assembly and thereby reduce rubbing and friction that occurs in some applications through plastic deformation of components that require precise dimensions.
[0312] Thus, for the application of a CVT belt formed of superimposed rings in cold rolled maraging steel and subjected to bending and tensile fatigue caused by the torque transmitted by the engine, the gap between each ring ensures lubrication of the assembly and does not allow plastic deformation that would damage the rings under cyclic stress. After each stress cycle, the nitrided material of the present invention undergoes less plastic deformation and does not cause cumulative plastic deformation of the component over time, which would deteriorate the fatigue life of the reference nitrided material over a longer period of time.
[0313] Figure 6 It was confirmed that the nitrided layer from Ref 1 has a greater plastic deformation at low loads (10 N) than the plastic deformation produced by the sample according to the invention. This is evidenced by the shift of the horizontal axis 0 of the different curves of the residual penetration depth.
[0314] The deformation of Ref 1 in the scratch test appears to be smaller than that of the steel of the invention (as shown by its relative indentation depth), but the deformation mechanisms involved are not exactly the same and the residual stresses after this loading do not produce the same effects. For example, although the deformation produced on Ref 1 during the test appears to be smaller (from the estimated indentation depth), the results after the test show an increased plastic component compared to the inventive sample, which is detrimental to the application that the invention is primarily intended for.
[0315] The indentation depth observed on the inventive sample proved to be essentially elastic, unlike Ref 1 which exhibited less rebound force at low loads.
[0316] Prior studies on maraging steels of the general type to which the present invention relates, particularly for use in CVT type drive belts, have not demonstrated those behavioral criteria in nitrided surfaces associated with controlled inclusion populations and mechanical properties inherent in the composition of the steel.
[0317] In general, the steels according to the invention show increased economic performance under different nitriding conditions and comparable or even increased performance properties compared to the prior art reference steels, provided that the nitrided layer is more easily controlled in terms of:
[0318] composition, especially with respect to the presence or absence of compound layers;
[0319] thickness;
[0320] The hardness level achievable under given nitriding conditions;
[0321] distribution, within the layer thickness, nitrogen content, type and distribution of precipitated phases, hardness level, residual stresses;
[0322] Reduced levels of plastic deformation (almost zero) induced in these nitrided layers under low load stresses;
[0323] The ease and economy of industrial implementation of nitriding, which obtains properties comparable to those of the reference steel grade, whether the nitriding is plasma nitriding or more particularly gas nitriding.
[0324] Preferred applications of the invention are in particular:
[0325] For products originating from hot-rolled products or hot-formed semi-finished products: general turbine shafts or transmission parts; and blades of rotating machinery (wind turbines, centrifuges, etc.);
[0326] For products derived from cold rolled sheet or strip: components of vehicle drive belts or components of rotating machinery such as machine tools, in particular automatic vehicle transmissions of the CVT type.
Claims
1. A steel having the following composition in weight percentage: 10.0%≤Ni≤24.5%; 1.0%≤MO≤12.0%; 1.0% ≤ CO ≤ 18.0%; 14.0%≤Mo+Co+Si+Mn+Cu+W+V+Nb+Zr+Y+Ta+Cr+C+Al+B+Ti+N≤29.0%; 21.5%≤Ni+CO+MO≤47.5%; Trace amount ≤Al≤4.0%; Trace amount ≤Ti≤0.1%; Trace amount ≤N≤0.010%; Trace amount ≤Si≤4.0%; 0.14%≤Mn≤13.0%; Trace ≤C≤0.03%; Trace ≤S≤0.0020%; Trace ≤P≤0.005%; Trace amount ≤ B ≤ 0.01%; Trace ≤H ≤ 0.0005%; Trace ≤O≤0.03%; Trace ≤Cr≤5.0%; Trace ≤Cu≤4%; Trace amount ≤ W ≤ 6.0%; Trace amount ≤ Zr ≤ 4.0%; Trace amount ≤Ca≤0.1%; Trace ≤Mg≤0.8%; Trace amount ≤ Nb ≤ 4.0%; Trace ≤V≤4.0%; Trace ≤Ta≤4.0%; Trace ≤ Y ≤ 4.0%; The rest is iron and impurities brought about by its manufacture; And characterized in that when the steel is in the form of a hot-working component, the 650mm 2 The inclusion population observed by image analysis of the polished surface and 800 mm2 of the polished surface in the form of the steel in the form of a cold-rolled plate does not contain non-metallic inclusions with an equivalent diameter greater than 10 μm.
2. A steel having the following composition in weight percentage: 10.0%≤Ni≤24.5%; 1.0%≤MO≤12.0%; 1.0% ≤ CO ≤ 18.0%; 14.0%≤Mo+Co+Si+Mn+Cu+W+V+Nb+Zr+Y+Ta+Cr+C+Al+B+Ti+N≤29.0%; 21.5%≤Ni+Co+MO≤47.5%; Trace amount ≤Al≤4.0%; Trace amount ≤Ti≤0.1%; Trace amount ≤N≤0.010%; Trace amount ≤Si≤4.0%; 0.14%≤Mn≤13.0%; Trace ≤C≤0.03%; Trace ≤S≤0.0020%; Trace ≤P≤0.005%; Trace amount ≤ B ≤ 0.01%; Trace ≤H ≤ 0.0005%; Trace ≤O≤0.03%; Trace ≤Cr≤5.0%; Trace ≤Cu≤4%; Trace amount ≤ W ≤ 6.0%; Trace amount ≤ Zr ≤ 4.0%; Trace amount ≤Ca≤0.1%; Trace ≤Mg≤0.8%; Trace amount ≤ Nb ≤ 4.0%; Trace ≤V≤4.0%; Trace ≤Ta≤4.0%; Trace ≤ Y ≤ 4.0%; The rest is iron and impurities brought about by its manufacture; And characterized in that when the steel is in the form of hot-rolled plate, the 650mm 2 The inclusion group observed by image analysis of the polished surface does not contain non-metallic inclusions with an equivalent diameter greater than 10 μm.
3. The steel according to claim 1 or 2, wherein: 0.14%≤Al+Si+Cu+Nb+Mn+V+Ta+Cr+W+C+B+Y+Zr+Ti+N≤8.0%.
4. The steel according to claim 1 or 2, wherein: Al+Cr≥0.17%.
5. The steel according to claim 1 or 2, wherein: The inclusion group does not contain non-metallic inclusions with an equivalent diameter greater than 8 μm.
6. A hot-worked steel product having the following composition in weight percent: 10.0%≤Ni≤24.5%; 1.0%≤Mo≤12.0%; 1.0%≤Co≤18.0%; 14.0%≤Mo+Co+Si+Mn+Cu+W+V+Nb+Zr+Y+Ta+Cr+C+Al+B+Ti+N≤29.0%; 21.5%≤Ni+Co+MO≤47.5%; Trace amount ≤Al≤4.0%; Trace amount ≤Ti≤0.1%; Trace amount ≤N≤0.010%; Trace amount ≤Si≤4.0%; 0.14%≤Mn≤13.0%; Trace ≤C≤0.03%; Trace ≤S≤0.0020%; Trace ≤P≤0.005%; Trace amount ≤ B ≤ 0.01%; Trace ≤H ≤ 0.0005%; Trace ≤O≤0.03%; Trace ≤Cr≤5.0%; Trace ≤Cu≤4%; Trace amount ≤ W ≤ 6.0%; Trace amount ≤ Zr ≤ 4.0%; Trace amount ≤Ca≤0.1%; Trace ≤Mg≤0.8%; Trace amount ≤ Nb ≤ 4.0%; Trace ≤V≤4.0%; Trace ≤Ta≤4.0%; Trace ≤ Y ≤ 4.0%; The rest is iron and impurities brought about by its manufacture; And it is characterized in that the inclusion group observed when the image analysis is performed on the 650 mm2 polished surface of the hot-processed component does not contain non-metallic inclusions with an equivalent diameter greater than 10 μm.
7. The hot worked steel product of claim 6, wherein: The hot worked steel product is heat treated.
8. A hot worked steel product according to claim 6 or 7, wherein: 0.14%≤Al+Si+Cu+Nb+Mn+V+Ta+Cr+W+C+B+Y+Zr+Ti+N≤8.0%.
9. A hot worked steel product according to claim 6 or 7, wherein: Al+Cr≥0.17%.
10. The hot worked steel product according to claim 6 or 7, having a martensitic structure of at least 70%, a tensile strength of 2030 MPa or more, a compensated yield strength of 2000 MPa or more, a uniform elongation of 1% or more, and a Vickers hardness of 285 Hv10 or more, the hardness being evaluated along a cross section of the hot worked product.
11. A hot worked steel product according to claim 6 or 7, characterised in that The hot worked steel product has a grain size of ASTM 5 or finer.
12. A hot worked steel product according to claim 6 or 7, characterised in that The hot worked steel product has a grain size of ASTM 10 or finer.
13. A hot worked steel product having the following composition in weight percent: 10.0%≤Ni≤24.5%; 1.0%≤Mo≤12.0%; 1.0%≤Co≤18.0%; 14.0%≤Mo+Co+Si+Mn+Cu+W+V+Nb+Zr+Y+Ta+Cr+C+Al+B+Ti+N≤29.0%; 21.5%≤Ni+Co+Mo≤47.5%; Trace amount ≤Al≤4.0%; Trace amount ≤Ti≤0.1%; Trace amount ≤N≤0.010%; Trace amount ≤Si≤4.0%; 0.14%≤Mn≤13.0%; Trace ≤C≤0.03%; Trace ≤S≤0.0020%; Trace ≤P≤0.005%; Trace amount ≤ B ≤ 0.01%; Trace ≤H ≤ 0.0005%; Trace ≤O≤0.03%; Trace ≤Cr≤5.0%; Trace ≤Cu≤4%; Trace amount ≤ W ≤ 6.0%; Trace amount ≤ Zr ≤ 4.0%; Trace amount ≤Ca≤0.1%; Trace ≤Mg≤0.8%; Trace amount ≤ Nb ≤ 4.0%; Trace ≤V≤4.0%; Trace ≤Ta≤4.0%; Trace ≤ Y ≤ 4.0%; The rest is iron and impurities brought about by its manufacture; And it is characterized in that the inclusion group observed when the image analysis is performed on the 650mm2 polished surface of the hot-rolled plate does not contain non-metallic inclusions with an equivalent diameter greater than 10μm.
14. A cold rolled sheet or strip made of steel, wherein: The steel has the following composition in weight percent: 10.0%≤Ni≤24.5%; 1.0%≤Mo≤12.0%; 1.0%≤Co≤18.0%; 14.0%≤Mo+Co+Si+Mn+Cu+W+V+Nb+Zr+Y+Ta+Cr+C+Al+B+Ti+N≤29.0%; 21.5%≤Ni+Co+Mo≤47.5%; Trace amount ≤Al≤4.0%; Trace amount ≤Ti≤0.1%; Trace amount ≤N≤0.010%; Trace amount ≤Si≤4.0%; 0.14%≤Mn≤13.0%; Trace ≤C≤0.03%; Trace ≤S≤0.0020%; Trace ≤P≤0.005%; Trace amount ≤ B ≤ 0.01%; Trace ≤H ≤ 0.0005%; Trace ≤O≤0.03%; Trace ≤Cr≤5.0%; Trace ≤Cu≤4%; Trace amount ≤ W ≤ 6.0%; Trace amount ≤ Zr ≤ 4.0%; Trace amount ≤Ca≤0.1%; Trace ≤Mg≤0.8%; Trace amount ≤ Nb ≤ 4.0%; Trace ≤V≤4.0%; Trace ≤Ta≤4.0%; Trace ≤ Y ≤ 4.0%; The rest is iron and impurities brought about by its manufacture; And the characteristic is that, for 800mm 2 The inclusion group observed by image analysis of the polished surface does not contain non-metallic inclusions with an equivalent diameter greater than 10 μm.
15. The cold rolled sheet or strip according to claim 14, wherein: 0.14%≤Al+Si+Cu+Nb+Mn+V+Ta+Cr+W+C+B+Y+Zr+Ti+N≤8.0%.
16. The cold rolled sheet or strip according to claim 14 or 15, wherein: Al+Cr≥0.17%.
17. The cold rolled sheet or strip according to claim 14 or 15, wherein: For 800mm 2 The inclusion group observed by image analysis of the polished surface does not contain non-metallic inclusions with an equivalent diameter greater than 8μm.
18. The cold-rolled sheet or strip according to claim 14, characterized in that: The cold-rolled sheet or strip has been subjected to at least one heat treatment after cold rolling to harden the material.
19. The cold rolled sheet or strip according to claim 14, 15 or 18, characterized in that: The cold-rolled sheet or strip has a tensile strength of 2030 MPa or higher, a compensated yield strength of 2000 MPa or higher, and a uniform elongation of 1% or higher.
20. The cold-rolled sheet or strip according to claim 14 or 15, characterized in that: The grain size of the cold rolled sheet or strip is ASTM 5 or finer.
21. The cold-rolled sheet or strip according to claim 14 or 15, characterized in that: The grain size of the cold rolled sheet or strip is ASTM 10 or finer.
22. A steel product, characterized in that The steel product is derived from a hot-worked steel product according to any one of claims 6 to 13 or from a cold-rolled sheet or strip according to any one of claims 14 to 21 and is characterized in that the steel product has been subjected to a surface treatment for improving dynamic strength.
23. The steel product according to claim 22, characterized in that The hot-worked steel product or the cold-rolled sheet or strip is hot-formed.
24. The steel product according to claim 22 or 23, characterized in that The surface treatment is selected from carburizing, gas nitriding, ion nitriding, carbonitriding and shot peening.
25. A heat-processed transmission component, characterized in that: The hot-worked transmission component comprises at least one element made from the hot-worked steel product according to any one of claims 6 to 13.
26. The hot-processed transmission component according to claim 25, characterized in that: The hot-processed transmission component is a turbine shaft.
27. A transmission belt, characterized in that: The drive belt comprises at least one element made of the cold-rolled sheet or strip material according to any one of claims 14 to 21, or at least one element made of a product derived from the cold-rolled sheet or strip material.
28. The drive belt according to claim 27, characterized in that The transmission belt is a CVT type automobile transmission belt.
Citation Information
Patent Citations
Method for making a strip or a workpiece cut out from a cold rolled maraging steel strip
EP1339880B1